Muslim-Christian Dialogue from Pakistani Perspective: Evaluation of the Contribution of Christian Study Center - Saeed, Riaz Ahmad (Journal of Islamic and Religious Studies, 2017)
The twentieth century is considered as the most notable era for interfaith dialogue and other interreligious activities among the followers of different faiths across the globe. A number of interfaith activities were launched to bring closer, especially, the adherents of the Abrahamic faiths: Jews, Christians and Muslims. Many Christian institutes and organizations are actively involved in such activities. We cannot ignore the role of Christian Study Centers situated across the globe, which are rendering considerable services in the field of interfaith dialogue. One of them is the Christian Study Center Rawalpindi (CSC), Pakistan, which is the focal subject of this research paper. The CSC has a long journey in the course of interfaith dialogue and harmony, as it was its objective since its commencement. The CSC was established in 1967 as an extension of HMI (Henry Martyn Institute, Hyderabad India) to promote interfaith dialogue, harmony and good relationship among the followers of different faiths in Pakistan. It is conceded; the Christian Study Center Rawalpindi has provided great services and contributed a lot to interfaith dialogue, harmony and peace in Pakistan. In this study the efforts were made to evaluate the 50 years dialogical activities of the Christian Study Center (CSC), Rawalpindi.